A New Genus and Species of Delphacini (Hemiptera: Fulgoromorpha: Delphacidae) Associated with Hydrophytic Plants in Argentina - Marino de Remes Lenicov, Ana María (2013)
A new delphacid genus and species from Argentina, Lepidelphax pistiae Remes Lenicov, gen. et sp. nov.(Hemiptera: Fulgoromorpha: Delphacidae: Delphacini), is described and illustrated, and biological, distribution and experimental host range data are provided. Males of the new genus are easily distinguished from all other Neotropical Delphacini by being pale cream to white in color with a distinctive pair of longitudinal stripes on the face and symmetrical dark brown to black spots on the thorax and abdomen; very slender, laterally compressed, with long legs, narrow and short vertex with a small sub-apical areola continued by a distinctively simple frontal median carina. It also has unique malegenital structures. Laboratory and field data indicate this species is a specialized herbivore that feeds and oviposits exclusively on Pistia stratiotes (Alismatales: Araceae), a floating macrophyte native to South America. Lepidelphax pistiae was found throughout the distribution of P. stratiotes in Argentina.